ANALYSIS OF MSME WORKING CAPITAL NEEDS STUDY ON TOLITOLI FERIKAR CHIPS BUSINESS - Selvina, Selvina; Mudatsir, Mudatsir; Wartha, Eva (STIE Mujahidin Tolitoli Development Economics Study Program, 2024)
This study aims to find out and analyze the Working Capital Needs of the Ferikar Tolitoli Chip Company. To get a high level of efficiency, companies must always consider all their financial decisions in order to operate according to existing needs. Of course, this is very related to the consideration of the use of working capital that must exist in a company, especially in the industrial world. Therefore, incorrect management of working capital will interfere with the company's operationalization which will later have an impact on the achievement of final profit. This study uses a quantitative research design. The data source is in the form of Primary, namely data obtained through observations, interviews, and documentation related to this research. The data analysis method used is the turnover method (the turnover speed of all working capital elements and working capital turnover days, the turnover speed, and the amount of working capital needed). Based on the results of the research and discussion, it can be concluded that the Working Capital Needs at the Tolitoli Ferrikar Chips Company are the speed of turnover of working capital elements in cash as much as 19.2 times, receivables as many as 12.6 times, raw materials as many as 21 times, goods in process as many as 32 times, while finished goods as many as 23.6 times so that all working capital elements owned by the Tolitoli ferikar chips company are 108.4 times for 1 year, and the working capital turnover day is 89 days. Meanwhile, the speed of working capital turnover of the Tolitoli ferry chip company is 4 times. The amount of working capital needed by the Tolitoli ferry chip company in 1 year is Rp. 150,000,000,-Keywords: Working Capital; Working Capital Needs; MSMEs; Chip Business